Printable biomaterials for 3D brain regenerative scaffolds: An in vivo biocompatibility assessment - Maylis Combeau; Nina Colitti; Julien Clauzel; Franck Desmoulin; Adrien Brilhault; Juliette Fitremann; Mickaël Chabbert; Matthew L. Becker; Sébastien Blanquer; Lorenne Robert; Melissa Parny; Isabelle Raymond-Letron; et al. (Regenerative Therapy)
Background: Brain regeneration after injury is a challenge being tackled by numerous therapeutic strategies in pre-clinical development. There is growing interest in scaffolds implanted in brain lesions. Developments in 3D printing offer the possibility of designing complex structures of varying compositions adapted to tissue anatomy. Methods: This feasibility study assessed the cerebral biocompatibility of four bioeliminable Digital Light Processing (DLP) printed materials in the rat model: gelatin methacrylate (GelMA), poly(ethylene glycol)diacrylate (PEGDA) mixed with GelMA (PEGDA-GelMA), poly(trimethylene carbonate) trimethacrylate (PTMC-tMA) and an ABA triblock copolymer of polypropylene fumarate-b-poly γ-methyl ε-caprolactone-b-polypropylene fumarate (P(PF-MCL-PF)). Their tolerance was compared to that of polydioxanone Ethicon (PDSII), a neurosurgery suture component commonly used in clinical practice. A one-month MRI and behavioral follow-up aided in safety assessment. Results: High-resolution T2 MRI imaging effectively captured the scaffold structures and demonstrated its non-invasive utility in monitoring degradability. PDSII served as a control of the acceptable inflammatory response to implantable foreign bodies. GelMA, PEGDA-GelMA and PTMC-tMA did not affect the permissive glial barrier, promoted cell migration, and neovascularization without additional perilesional microglial inflammation (median mean of 6.5 %, compared to 8.2 % for the PDSII control). However, the GelMA scaffold core was not colonized and allowed a limited neuronal progenitors recruitment. The rigidity of PTMC-tMA facilitated insertion, but posed histological issues. The brain hardly reacted to the P(PF-MCL-PF). Conclusion: All these materials can serve as a basis for brain regeneration. PEGDA-GelMA emerged as a promising candidate for intracerebral implantation, combining biophysical and bioprinting advantages while maintaining an acceptable level of inflammation compared with clinically used suture, paving the way for innovative therapies.